PERAN DAN KOLABORASI STAKEHOLDER PADA PERKEMBANGAN PARIWISATA HERITAGE DI KAWASAN SIWA PLATEAU DAERAH ISTIMEWA YOGYAKARTA: [Stakeholder's Role and Collaboration on Heritage Tourism Development at Siwa Plateu Area Special Region of Yogyakarta] - Jusman Mahmud (Berkala Arkeologi Sangkhakala, 2021)
This paper investigates variety of role and collaboration of stakeholders involved with heritage tourism development in Siwa Plateau Area, Special Region of Yogyakarta Province in order to better understand whether and how those roles and collaborations reflect an effort to find a balance related to inherent contradictions in the concepts of heritage (conservation/preservation) and tourism (change/development). The method used was qualitative inductive with primary data obtained by survey, interview and observation. The variety of role and collaboration forms of stakeholders reflects at least three main aspects with variety of nuance. First is heritage protection and development control. Second is being partners in managing heritage as a tourist attraction/destination. Third is that there are active efforts to involve local communities as key players in heritage tourism development in the region.